The role of the Soil Science Department of Kharkiv National Agrarian University named after V.V.Dokuchayev in the development of soil science and education in Ukraine - Degtyarev, V.V.; Tykhonenko, D.G.; Gavva, D.V. (AgroChemistry and Soil Science, 2018)
The history of the Soil Science Department of the Kharkiv National Agrarian University named after V.V. Dokuchaev from the moment of foundation (1894) till nowadays. V.V. Dokuchaev was the founder of the Soil Science Department (the first in the world), and M.M. Sybirtsev was the first head. The activity of the department is related to the creation of the first classification of soils, the creation of the first textbook on soil science and laying the foundations of the methodology of soil science on the basis of genetic and evolution. The article reveals the achievements of the teaching staff of the department during the almost 125-year period; it is shown the significance of studies in the field of soil science for the development of knowledge both in Ukraine and in many other countries, for which a large number of specialists and scientists have been trained.